Concussion symptoms experienced during driving may influence driving habits. (5th January 2021) - D'Silva, L.; Devos, H.; Hunt, S. L.; Chen, J.; Smith, D.; Rippee, M. A.
ABSTRACT: Objective : To examine the symptoms experienced and the change in driving habits in individuals with concussion. Materials and methods : A survey was created by a team of rehabilitation professionals who see persons with concussion in their clinics. The survey captured demographics, mechanism of injury, date of injury, symptoms experienced during driving, if drivers felt safe when driving, and changes in driving habits since the concussion. Non-parametric tests were used to compare symptoms experienced and driving habits across three groups which were created based on time since injury. Results : Of the 140 participants, 74% (104/140) had resumed driving after concussion; of these 27% (28/104) reported that they felt unsafe while driving. Forty-four per cent (46/104) experienced symptoms while driving, of which headache, and difficulty concentrating were the most common symptoms experienced throughout the concussion spectrum (acute to chronic phase). Most drivers (78/104, 75%) with concussion had changed their driving habits by driving less often and shorter distances, and by avoiding nighttime driving and heavy traffic areas. Conclusions : Headache and concentration problems were experienced by drivers regardless of the time since injury. Most drivers had made changes to their driving habits. Clinicians should consider the symptom burden patients experience and discuss driving restrictions to ensure driving safety.